Targeting the SARS-CoV-2-spike protein: from antibodies to miniproteins and peptides. Issue 2 (17th December 2020) - Pomplun, Sebastian
Abstract : Fighting COVID-19 with high affinity reagents: this review article summarizes the discovery of several classes of (bio) molecules targeting the SARS-CoV-2 spike protein. Abstract : Coronavirus disease-19, caused by the novel β-coronavirus SARS-CoV-2, has created a global pandemic unseen in a century. Rapid worldwide efforts have enabled the characterization of the virus and its pathogenic mechanism. An early key finding is that SARS-CoV-2 uses spike proteins, the virus' most exposed structures, to bind to human ACE2 receptors and initiate cell invasion. Competitive targeting of the spike protein is a promising strategy to neutralize virus infectivity. This review article summarizes the discovery, binding modes and eventual applications of several classes of (bio)molecules targeting the spike protein: antibodies, nanobodies, soluble ACE2 variants, miniproteins, peptides and small molecules.